Complementary Methodology for Energy Efficiency Ratio-Based Assessments with Change-Point Model Parameters - Kim, Hye Gi; Kim, Sun Sook (Buildings, 2023)
The energy consumption of existing buildings is not only affected by their physical features but also by their business activities (e.g., operating hours, number of workers, and climate). Energy Star’s energy efficiency ratio (EER) is a key energy performance indicator that has been used for more than 20 years. This method normalizes operation characteristics by calculating the estimated energy consumption of business activities using regression models and comparing it with the actual energy consumption. However, EER-based assessment is limited by the lack of information regarding the reasons for the evaluation results. This study proposes a balanced method for explaining the reasons underlying energy efficiency levels while maintaining the existing EER assessment system. The method constitutes data collection, EPI derivation, and energy performance assessment, utilizing the parameters of the change-point linear model (CPM) as an additional EPI to provide descriptive information. The results are summarized to provide a checklist guide for retrofitting, and additional energy saving potential for buildings with low and high scores can be identified by comparing the EER scores and CPM parameters. The proposed method shows that it is possible to interpret the energy efficiency assessment results by comparing CPM parameters, while maintaining the EER score.
Keywords: Business activities; Change-point linear model; Change-point models; Change-points; Energy efficiency ratio; Energy performance assessments; Energy performance indicators; Energy-consumption; Linear modeling; Modeling parameters; change-point linear model; energy efficiency ratio; energy performance assessment; energy performance indicator